Biomass – An Endless Source of Renewable Energy - Chandra, Yogender Pal; Singh, Arashdeep; Singh, Gurtej; Ramashwar, Rudra (Asian Review of Mechanical Engineering, 2016)
Energy demand in India is increasing continuously due to sharp growth in population and industrial development. Major demand of electricity is fulfilled by conventional energy resources like coal, oil, gas etc. About 13% of installed capacity in India is obtained from renewable energy sources. India being an agricultural rich country has a huge stockpile of biomass which can be used as a potential source to obtain renewable energy in the future for providing energy access to all. Biomass comprises of agricultural waste like woody waste, rice husk, cotton straw, industrial waste, household waste and human & animal waste. Present research work has been put forward to discuss about potential of biomass based power generation in India, different processes to obtain energy from biomass, future prospectus of biomass based power generation systems. Different slurry based and gasification system designs existing today are elaborated in this paper. These systems are energy efficient and environmentally & economically clean to generate heat and electricity. If used on a large scale these systems can solve cooking problems and may provide energy access in rural areas of India through distributed systems.